Anthraquinone analogues with inhibitory activities against influenza a virus from Polygonatum odoratum. Issue 8 (15th July 2021) - Pang, Xu; Zhao, Jian-Yuan; Liu, Ning; Chen, Ming-Hua; Zheng, Wei; Zhang, Jie; Chen, Xiao-Juan; Cen, Shan; Yu, Li-Yan; Ma, Bai-Ping
Abstract: Three anthraquinone analogues (1 –3 ) were isolated by phytochemical work on EtOAc-soluble ingredients extracted from the roots of Polygonatum odoratum . The structures of all isolates were elucidated by NMR, MS and CD experiments, of which 1 (polygodoquinone A) was identified as a new anthraquinone derivative. Specifically, 1 represents an unusual structure composed of a naphthoquinone derivative linked to an anthraquinone via a C-C bond. 1 –3 exhibited remarkable influenza A virus inhibitory activity with IC50 values of 11.4, 11.0, and 2.3 μM, respectively, which were better than ribavirin as the positive control. Graphical Abstract: UF0001